Patterns of multilevel parliamentary relations. Varieties and dynamics in the EU and other federations. Issue 4 (11th April 2017) - Benz, Arthur
ABSTRACT: Multilevel relations between parliaments have drawn attention in European studies, but scholars rarely have studied them in a comparative perspective. Based on a framework distinguishing various patterns of multilevel parliamentary relations, comparative research on Canada, Germany and the EU reveals particular dynamics. Multilevel structures provide opportunities for executives, but also for parliaments to extend or maintain their power. Accordingly, rather than a stable constellation, an ever changing interplay of parliaments and executives at the different levels affects the quality of democracy in federations. From this perspective, neither the concept of executive federalism nor an optimistic expectation of a multilevel parliamentary democracy appears appropriate to describe real constellations of power. In general, multilevel parliamentary relations can contribute to balance executive and parliamentary powers and make parliamentary control of multilevel governance more effective. Yet the real challenge is to make these relations robust.